Variety of narrow-leaved lupine (Lupinus angustifolius L.) Mezenat - O. G. Lysenko; V. F. Lysenko; E. N. Pasynkova (Аграрная наука Евро-Северо-Востока, 2022)
The purpose of the study was to create of an early ripening variety of narrow-leaved lupine with a seed and green mass yield above the standard, resistant to unfavorable biotic and abiotic environmental factors in the North-West region of the Russian Federation. As the result of many years of breeding, an early ripening variety of narrow-leaved lupine Metsenat has been developed. In a competitive varietal trial conducted in the conditions of the Leningrad Region, the seed yield of the variety Metsenat averaged 4.3 t/ha in 2015-2017 that was 1.1 t/ha higher than the standard (Kristall), the yield of green hay was 48.4 t/ha (13.9 t/ha higher than the standard). According to the results of the structural analysis of plants, the variety Metsenat was characterized by an increased number of seeds per plant (90.4 pcs.) and a good seeding of the beans (4.4 pcs.). It is a variety of universal use, with a low content of alkaloids (0.0072 %), it is technological, resistant to lodging (7 points), to cracking of beans and shedding of seeds on the vine, resistant to anthracnose (9 points). It is characterized by a rapid growth rate of plants in the initial period of vegetation. In 2018 the Metsenat variety was included into the State Register of Breeding Achievements of the Russian Federation approved for use in agricultural production in 12 regions (Patent No. 9559).